2023
DOI: 10.3390/medicina59061006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravascular Photobiomodulation on Insomnia, Muscle Soreness, and Biochemistry Profiles: An Eight-Year Retrospective Cohort

Abstract: Background: Although cognitive-behavioral therapy is the first-line treatment for insomnia, pharmacotherapy is often prescribed to treat insomnia and related symptoms. In addition, muscle relaxants are commonly prescribed to alleviate muscle soreness when the pain is unbearable. However, pharmacotherapy can lead to numerous side effects. The non-drug strategy intravascular laser irradiation of blood (iPBM) has been advocated to improve pain, wound healing, blood circulation, and blood cell function to relieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Despite these benefits, ILIB has not been used to treat migraine. Our previous case report showed that ILIB could improve perfusion of the contralateral cerebellum during diaschisis after an ischemic stroke event [ 17 ], or traumatic brain injury [ 14 ], and improve sleep quality in patients with musculoskeletal pain [ 18 , 19 ]. In the current study, we demonstrated ILIB-associated improvements in pain, cognition, disability, insomnia, and rCBF in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, ILIB has not been used to treat migraine. Our previous case report showed that ILIB could improve perfusion of the contralateral cerebellum during diaschisis after an ischemic stroke event [ 17 ], or traumatic brain injury [ 14 ], and improve sleep quality in patients with musculoskeletal pain [ 18 , 19 ]. In the current study, we demonstrated ILIB-associated improvements in pain, cognition, disability, insomnia, and rCBF in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-Resonator Wireless Inductive Power Link for Wearables on the 2D Surface and Implants in 3D Space of the Human Body T Intravascular Photo-biomodulation (iPBM), or Intravascular Laser Irradiation of Blood Therapy (ILIB, using laser light through optical fibers inserted into veins). These are all proven low/non-invasive treatment methods with potential benefits such as wound healing, pain relief, anti-inflammatory responses, anti-edema effects, nerve regrowth, tissue repair, and regeneration [31]- [33]. They enhance blood circulation and optimize blood cell functionality, ensuring beneficial effects in reducing inflammation, enhancing antioxidants, and improving hemodynamic parameters.…”
Section: Member Ieeementioning
confidence: 99%